Wear-resistant antirust Teflon coating and preparation method thereof
By using porous alumina nanospheres and silica coated with modified Zn/Fe particles in Teflon coatings, combined with irradiation-induced grafting reaction, the uniformity and rust prevention problems of the coating when adding hard particles are solved. , realizes efficient wear resistance and rust resistance, and is suitable for protection of high wear-resistant environments.
Patent Information
- Application Number
- CN202411823319.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-12
AI Technical Summary
现有耐磨特氟龙涂料在添加硬质颗粒时难以均匀喷涂,导致涂层内部显微裂纹和颗粒团聚,降低了疏水性能和磨损稳定性,同时缺乏防锈功能,难以在高耐磨环境 中有效保护基材。
The modified Zn/Fe particles are coated with porous alumina nanospheres and silicon oxide. We prepare wear-resistant and anti-rust Teflon coatings through deposition, reduction, modification and hydrolysis, and use the mesoporous structure and oxide layer to improve the coating. Wear resistance and rust resistance, and compatibility is enhanced by irradiation inducing graft reaction of Teflon polymer chains.
The prepared coating has good lubrication conditions and mechanical resistance, excellent wear resistance, scratch resistance, medium resistance and high temperature resistance, and can effectively resist high wear resistance environments such as sliding friction and impact friction, and make up for contact. Wear defects caused by surface friction and provide long-term protection.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a wear-resistant and rust-proof Teflon coating and a preparation method thereof. Background Art
[0002] Teflon coating is an industrial coating with polytetrafluoroethylene (PTFE) as the main component. It has many excellent properties, such as non-stickiness, heat resistance, sliding, moisture resistance, wear resistance, and corrosion resistance, which makes it widely used in many industries.
[0003] As a protective functional coating, wear-resistant coating has the characteristics of low friction coefficient on the coating surface, high load bearing capacity, and strong mechanical resistance. Therefore, it can effectively reduce the friction between interfaces when subjected to external forces, reduce the intensity of wear and the strength of resistance to wear, and play a role in protecting the substrate and extending its service life. It is widely used in aerospace, vehicles, ships, instruments, machine tool industries, etc. In recent years, as renewable energy has received more and more attention, the demand for wear-resistant coatings in the energy field has increased dramatically, especially in wind turbine blades, nuclear reactor containment, dam structures, turbines, etc.
[0004] At present, wear-resistant coatings at home and abroad mainly achieve their wear-resistant effects in two ways: one is to add lubricants such as graphite, molybdenum disulfide, graphene and its derivatives to the coating to make the coating have good lubrication conditions, and transfer the friction pair to the internal friction of the lubricant during interface contact, thereby reducing the friction between the contact surfaces and achieving lubrication and friction reduction; the second is to add wear-resistant aggregates such as aluminum oxide, silicon carbide, and silicon dioxide to the coating to improve the strength of the coating, which can effectively resist frequent external wear, high-speed erosion, and violent collisions.
[0005] In addition, the matrix resin also plays a decisive role in the wear resistance of the coating.
[0006] Adding hard particles to Teflon coatings to resist wear has become an effective method. However, if the hard particles are too large, it is difficult to spray evenly and may cause micro cracks inside the coating. If the particles are too small, the surface energy increases, causing the particles to agglomerate and cannot be mixed evenly. Both greatly reduce the hydrophobicity and wear stability of the coating. At the same time, the presence of micro cracks also makes it easier for corrosive media to invade, destroy the coating structure, and further damage the wear performance of the coating. Therefore, improving the dispersibility of additives and avoiding the agglomeration of particles inside the coating after spraying and the generation of cracks near the additives have become key factors in improving the wear resistance of the coating. At the same time, the Teflon coating produced is also required to have good anti-rust function. Summary of the invention
[0007] The purpose of the present invention is to propose a wear-resistant and rust-proof Teflon coating and a preparation method thereof, which has good lubrication conditions and anti-mechanical effect, excellent wear resistance, scratch resistance, medium resistance, high temperature resistance and other properties, can effectively resist high wear-resistant environments such as sliding friction, impact friction, cavitation friction, etc., can not only make up for the wear defects caused by friction between the two contact surfaces, but also enable the two relatively moving surfaces to have good lubrication and friction reduction effects, solve the friction and wear problems, and protect the substrate for a long time.
[0008] The technical solution of the present invention is achieved in this way:
[0009] The present invention provides a method for preparing a wear-resistant and rust-proof Teflon coating, comprising the following steps:
[0010] S1. Preparation of porous alumina nanospheres: adding aluminum sulfate and urea to water, adding a porogen, heating and stirring the reaction, adjusting the pH value of the solution, continuing to stir the reaction, centrifuging, washing, drying, and calcining to obtain porous alumina nanospheres; the mass ratio of aluminum sulfate, urea, and porogen is 3-5:7-10:0.1-0.2;
[0011] S2. ZnO / Fe2O3 deposition: adding porous alumina nanospheres to water, adding zinc salt and iron salt, stirring and mixing, adding citric acid, heating and stirring, centrifuging, washing, drying, and calcining to obtain ZnO / Fe2O3 deposited porous alumina nanospheres; the mass ratio of the porous alumina nanospheres, zinc salt, iron salt, and citric acid is 10:2-3:1-2:4-7;
[0012] S3 reduction: The ZnO / Fe2O3 deposited porous alumina nanospheres were reduced by hydrogen to obtain Zn / Fe deposited porous alumina nanospheres;
[0013] S4 modification: adding Zn / Fe deposited porous alumina nanospheres to ethanol, adding a silane coupling agent, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified Zn / Fe deposited porous alumina nanospheres; the mass ratio of the Zn / Fe deposited porous alumina nanospheres to the silane coupling agent is 10:3-5;
[0014] S5. Hydrolysis: The modified Zn / Fe deposited porous alumina nanospheres were added to water and stirred for hydrolysis to obtain silica-coated modified Zn / Fe deposited porous alumina nanospheres;
[0015] S6. Graft modification of Teflon: adding polytetrafluoroethylene powder to Augeo SL-191 solvent, adding glycidyl methacrylate, an inhibitor and a sensitizer under irradiation conditions, introducing an inert gas, heating and stirring the reaction, extracting with acetone after the reaction, and drying to obtain a modified Teflon powder; the mass ratio of the polytetrafluoroethylene powder, glycidyl methacrylate, inhibitor and sensitizer is 10:2-3:0.01-0.02:0.02-0.05;
[0016] S7. Preparation of wear-resistant and rust-proof Teflon coating: adding modified Teflon powder and silica-coated modified Zn / Fe deposited porous alumina nanospheres to Teflon primer, stirring and reacting to obtain wear-resistant and rust-proof Teflon coating; the mass ratio of the modified Teflon powder, silica-coated modified Zn / Fe deposited porous alumina nanospheres and Teflon primer is 10:4-7:70-80.
[0017] As a further improvement of the present invention, the porogen in step S1 is selected from at least one of hexadecyltrimethylammonium chloride, hexadecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium bromide, the temperature of the heating and stirring reaction is 60-70°C, the time is 30-50min, the pH value of the solution is adjusted to 9-10, the time of continuing the stirring reaction is 90-120min, and the temperature of the calcination is 600-700°C, and the time is 1-2h.
[0018] As a further improvement of the present invention, the heating and stirring temperature in step S2 is 85-95°C, the heating and stirring time is 1-3h, the calcination temperature is 400-500°C, the calcination time is 1-3h, the zinc salt is zinc chloride or zinc nitrate, and the iron salt is at least one of ferric chloride, ferric nitrate, and ferric sulfate.
[0019] As a further improvement of the present invention, the temperature of the hydrogen reduction in step S3 is 1100-1200° C. and the time is 2-4 hours.
[0020] As a further improvement of the present invention, the silane coupling agent in step S4 is at least one of KH550, KH602, and KH792.
[0021] As a further improvement of the present invention, the silane coupling agent is a mixture of KH602 and KH792 in a mass ratio of 2-4:3-5, and the temperature of the heating and stirring reaction is 40-50° C. and the time is 1-2 h.
[0022] As a further improvement of the present invention, the stirring hydrolysis in step S5 is carried out at a temperature of 40-50° C. and for a time of 7-10 h.
[0023] As a further improvement of the present invention, the temperature of the irradiation conditions in step S6 is 100-150°C, the total irradiation dose is 12-15 kGy, the inhibitor is ammonium ferrous sulfate, the sensitizer is concentrated sulfuric acid, the temperature of the heating and stirring reaction is 60-70°C, and the time of the heating and stirring reaction is 3-5h.
[0024] As a further improvement of the present invention, the stirring reaction time in step S7 is 10-12 hours.
[0025] The present invention further protects a wear-resistant and rust-proof Teflon coating, which is prepared by the above-mentioned preparation method of the wear-resistant and rust-proof Teflon coating.
[0026] The present invention has the following beneficial effects:
[0027] The invention prepares a mesoporous alumina nanosphere, the mesoporous structure forms a large specific surface area, promotes the surface deposition of ZnO and Fe2O3, and then is reduced to Zn and Fe through hydrogen gas, and forms a dense oxide layer after oxidation, which can well protect the substrate from rusting. At the same time, the surface is modified by a silane coupling agent with amino groups, so that not only the surface of the prepared modified Zn / Fe deposited porous alumina nanosphere has amino groups, but also contains a silane structure, and forms a silicon oxide layer under the hydrolysis of water, which further improves the wear resistance and mechanical properties of the coating, and also improves the high temperature resistance of the coating.
[0028] The invention uses electron beam or gamma ray irradiation to break CC bonds and CF on the Teflon polytetrafluoroethylene chain to generate free radicals, and utilizes the free radicals to initiate a grafting reaction of glycidyl methacrylate monomer on the surface of the Teflon polytetrafluoroethylene, thereby improving the polarity of PTFE and further increasing its compatibility and reactivity with other substances. The grafted modified Teflon powder can undergo a ring-opening reaction with silicon oxide-coated modified Zn / Fe deposited porous alumina nanospheres with amino groups on the surface, thereby enabling the silicon oxide-coated modified Zn / Fe deposited porous alumina nanospheres to be very evenly dispersed in the Teflon coating, thereby improving the compatibility of the inorganic particles, thereby greatly improving the mechanical properties, wear resistance, rust resistance, medium resistance and other characteristics of the coating.
[0029] The Augeo SL-191 used in the present invention is a new type of hydrophilic and lipophilic, environmentally friendly solvent developed by Rhodia Company. It has a high boiling point, is colorless and odorless, has a low volatilization rate, and is non-toxic to human health and the environment.
[0030] The coating prepared by the present invention is dense after being cured into a film, has good lubrication conditions and anti-mechanical effect, excellent wear resistance, scratch resistance, medium resistance, high temperature resistance and other properties, can effectively resist high wear-resistant environments such as sliding friction, impact friction, cavitation friction, etc., can not only make up for the wear defects of the two contact surfaces caused by friction, but also enable the two relatively moving surfaces to have good lubrication and friction reduction effects, solve the friction and wear problems, and protect the substrate for a long time. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Polytetrafluoroethylene micropowder, water content <0.05%, was purchased from Shenyang Wuliang Technology Co., Ltd.; Teflon primer 420G-703 was purchased from Chemours; Augeo SL-191 was purchased from Rhodia.
[0033] Example 1
[0034] This embodiment provides a method for preparing a wear-resistant and rust-proof Teflon coating, comprising the following steps:
[0035] S1. Preparation of porous alumina nanospheres: 30 g aluminum sulfate and 70 g urea were added to 2 L water, 1 g hexadecyl dimethyl benzyl ammonium chloride was added, the mixture was heated to 60°C, stirred for 30 min, the pH value of the solution was adjusted to 9, the stirring reaction time was continued for 90 min, the mixture was centrifuged, washed, dried, and calcined at 600°C for 1 h to obtain porous alumina nanospheres;
[0036] S2. Deposition of ZnO / Fe2O3: 10 g of porous alumina nanospheres were added to 200 mL of water, 2 g of zinc chloride and 1 g of ferric chloride were added, the mixture was stirred and evenly mixed, 4 g of citric acid was added, the mixture was heated to 85°C, stirred for 1 h, centrifuged, washed, dried, and calcined at 400°C for 1 h to obtain ZnO / Fe2O3 deposited porous alumina nanospheres;
[0037] S3. Reduction: The ZnO / Fe2O3 deposited porous alumina nanospheres were heated to 1100°C and reduced with hydrogen for 2h to obtain Zn / Fe deposited porous alumina nanospheres;
[0038] S4. Modification: 10 g of Zn / Fe deposited porous alumina nanospheres were added to 200 mL of ethanol, 3 g of a silane coupling agent was added, the mixture was heated to 40°C, stirred for 1 h, centrifuged, washed, and dried to obtain modified Zn / Fe deposited porous alumina nanospheres;
[0039] The silane coupling agent is a mixture of KH602 and KH792, with a mass ratio of 2:3;
[0040] S5. Hydrolysis: 10 g of modified Zn / Fe deposited porous alumina nanospheres were added to 100 mL of water and stirred for hydrolysis at 40 ° C for 7 h to obtain silica-coated modified Zn / Fe deposited porous alumina nanospheres;
[0041] S6. Graft modification of Teflon: 10 g of polytetrafluoroethylene powder was added to 200 mL of Augeo SL-191 solvent. Under irradiation conditions, the temperature was 100 ° C, the total irradiation dose was 12 kGy, 2 g of glycidyl methacrylate, 0.01 g of ammonium ferrous sulfate and 0.02 g of concentrated sulfuric acid were added, nitrogen was introduced, heated to 60 ° C, stirred for 3 h, and after the reaction was completed, extracted with acetone for 24 h and dried to obtain modified Teflon powder;
[0042] S7. Preparation of wear-resistant and rust-proof Teflon coating: 10 g of modified Teflon powder and 4 g of silica-coated modified Zn / Fe deposited porous alumina nanospheres were added to 70 g of Teflon primer, and the mixture was stirred for 10 h to obtain a wear-resistant and rust-proof Teflon coating.
[0043] Example 2
[0044] This embodiment provides a method for preparing a wear-resistant and rust-proof Teflon coating, comprising the following steps:
[0045] S1. Preparation of porous alumina nanospheres: 50 g aluminum sulfate and 100 g urea were added to 2 L water, 2 g hexadecyltrimethylammonium bromide was added, the mixture was heated to 70°C, stirred for 50 min, the pH value of the solution was adjusted to 10, the mixture was stirred for 120 min, centrifuged, washed, dried, and calcined at 700°C for 2 h to obtain porous alumina nanospheres;
[0046] S2. Deposition of ZnO / Fe2O3: 10 g of porous alumina nanospheres were added to 200 mL of water, 3 g of zinc chloride and 2 g of ferric sulfate were added, the mixture was stirred and evenly mixed, 7 g of citric acid was added, the mixture was heated to 95°C, stirred for 3 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain ZnO / Fe2O3 deposited porous alumina nanospheres;
[0047] S3. Reduction: The ZnO / Fe2O3 deposited porous alumina nanospheres were heated to 1200°C and reduced with hydrogen for 4 h to obtain Zn / Fe deposited porous alumina nanospheres;
[0048] S4. Modification: 10 g Zn / Fe deposited porous alumina nanospheres were added to 200 mL ethanol, 5 g silane coupling agent was added, the mixture was heated to 50°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified Zn / Fe deposited porous alumina nanospheres;
[0049] The silane coupling agent is a mixture of KH602 and KH792, with a mass ratio of 4:5;
[0050] S5. Hydrolysis: 10 g of modified Zn / Fe deposited porous alumina nanospheres were added to 100 mL of water and stirred for hydrolysis at 50 ° C for 10 h to obtain silica-coated modified Zn / Fe deposited porous alumina nanospheres;
[0051] S6. Graft modification of Teflon: 10 g of polytetrafluoroethylene powder was added to 200 mL of Augeo SL-191 solvent. Under irradiation conditions, the temperature was 150 ° C, the total irradiation dose was 15 kGy, 3 g of glycidyl methacrylate, 0.02 g of ammonium ferrous sulfate and 0.05 g of concentrated sulfuric acid were added, nitrogen was introduced, heated to 70 ° C, stirred for 5 h, and after the reaction was completed, extracted with acetone for 24 h and dried to obtain modified Teflon powder;
[0052] S7. Preparation of wear-resistant and rust-proof Teflon coating: 10 g of modified Teflon powder and 7 g of silica-coated modified Zn / Fe deposited porous alumina nanospheres were added to 80 g of Teflon primer, and the mixture was stirred for 12 h to obtain a wear-resistant and rust-proof Teflon coating.
[0053] Example 3
[0054] This embodiment provides a method for preparing a wear-resistant and rust-proof Teflon coating, comprising the following steps:
[0055] S1. Preparation of porous alumina nanospheres: 40 g aluminum sulfate and 80 g urea were added to 2 L water, 1.5 g hexadecyltrimethylammonium chloride was added, heated to 65°C, stirred for 40 min, the pH value of the solution was adjusted to 9.5, the stirring reaction was continued for 100 min, centrifuged, washed, dried, and calcined at 650°C for 1.5 h to obtain porous alumina nanospheres;
[0056] S2. Deposition of ZnO / Fe2O3: 10 g of porous alumina nanospheres were added to 200 mL of water, 2.5 g of zinc nitrate and 1.5 g of ferric nitrate were added, the mixture was stirred and mixed evenly, 5.5 g of citric acid was added, the mixture was heated to 90°C, stirred for 2 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to obtain ZnO / Fe2O3 deposited porous alumina nanospheres;
[0057] S3. Reduction: The ZnO / Fe2O3 deposited porous alumina nanospheres were heated to 1150°C and reduced with hydrogen for 3h to obtain Zn / Fe deposited porous alumina nanospheres;
[0058] S4. Modification: 10 g of Zn / Fe deposited porous alumina nanospheres were added to 200 mL of ethanol, 4 g of a silane coupling agent was added, the mixture was heated to 45 ° C, stirred for 1.5 h, centrifuged, washed, and dried to obtain modified Zn / Fe deposited porous alumina nanospheres;
[0059] The silane coupling agent is a mixture of KH602 and KH792, with a mass ratio of 3:4;
[0060] S5. Hydrolysis: 10 g of modified Zn / Fe deposited porous alumina nanospheres were added to 100 mL of water and stirred for hydrolysis at 45 ° C for 8 h to obtain silica-coated modified Zn / Fe deposited porous alumina nanospheres;
[0061] S6. Graft modification of Teflon: 10 g of polytetrafluoroethylene powder was added to 200 mL of Augeo SL-191 solvent. Under irradiation conditions, the temperature was 125 ° C, the total irradiation dose was 13 kGy, 2.5 g of glycidyl methacrylate, 0.015 g of ammonium ferrous sulfate and 0.04 g of concentrated sulfuric acid were added, nitrogen was introduced, heated to 65 ° C, stirred for 4 hours, and after the reaction was completed, extracted with acetone for 24 hours and dried to obtain modified Teflon powder;
[0062] S7. Preparation of wear-resistant and rust-proof Teflon coating: 10 g of modified Teflon powder and 5 g of silica-coated modified Zn / Fe deposited porous alumina nanospheres were added to 75 g of Teflon primer, and the mixture was stirred for 11 h to obtain a wear-resistant and rust-proof Teflon coating.
[0063] Example 4
[0064] Compared with Example 3, the difference is that the silane coupling agent is a single KH602.
[0065] Example 5
[0066] Compared with Example 3, the difference is that the silane coupling agent is a single KH792.
[0067] Comparative Example 1
[0068] Compared with Example 3, the difference is that steps S4 and S5 are not performed.
[0069] The details are as follows:
[0070] S1. Preparation of porous alumina nanospheres: 40 g aluminum sulfate and 80 g urea were added to 2 L water, 1.5 g hexadecyltrimethylammonium chloride was added, heated to 65°C, stirred for 40 min, the pH value of the solution was adjusted to 9.5, the stirring reaction was continued for 100 min, centrifuged, washed, dried, and calcined at 650°C for 1.5 h to obtain porous alumina nanospheres;
[0071] S2. Deposition of ZnO / Fe2O3: 10 g of porous alumina nanospheres were added to 200 mL of water, 2.5 g of zinc nitrate and 1.5 g of ferric nitrate were added, the mixture was stirred and mixed evenly, 5.5 g of citric acid was added, the mixture was heated to 90°C, stirred for 2 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to obtain ZnO / Fe2O3 deposited porous alumina nanospheres;
[0072] S3. Reduction: The ZnO / Fe2O3 deposited porous alumina nanospheres were heated to 1150°C and reduced with hydrogen for 3h to obtain Zn / Fe deposited porous alumina nanospheres;
[0073] S4. Graft modification of Teflon: 10 g of polytetrafluoroethylene powder was added to 200 mL of Augeo SL-191 solvent. Under irradiation conditions, the temperature was 125°C, the total irradiation dose was 13 kGy, 2.5 g of glycidyl methacrylate, 0.015 g of ammonium ferrous sulfate and 0.04 g of concentrated sulfuric acid were added, nitrogen was introduced, heated to 65°C, stirred for 4 h, and after the reaction was completed, extracted with acetone for 24 h and dried to obtain modified Teflon powder;
[0074] S5. Preparation of wear-resistant and rust-proof Teflon coating: 10 g of modified Teflon powder and 5 g of Zn / Fe deposited porous alumina nanospheres were added to 75 g of Teflon primer, and the mixture was stirred and reacted for 11 h to obtain a wear-resistant and rust-proof Teflon coating.
[0075] Comparative Example 2
[0076] Compared with Example 3, the difference is that zinc nitrate is not added in step S2.
[0077] The details are as follows:
[0078] S2. Deposition of Fe2O3: Add 10 g of porous alumina nanospheres into 200 mL of water, add 4 g of ferric nitrate, stir and mix evenly, add 5.5 g of citric acid, heat to 90°C, stir for 2 h, centrifuge, wash, dry, and calcine at 450°C for 2 h to obtain Fe2O3 deposited porous alumina nanospheres.
[0079] Comparative Example 3
[0080] Compared with Example 3, the difference is that no ferric nitrate is added in step S2.
[0081] The details are as follows:
[0082] S2. Deposition of ZnO: Add 10 g of porous alumina nanospheres into 200 mL of water, add 4 g of zinc nitrate, stir and mix evenly, add 5.5 g of citric acid, heat to 90°C, stir for 2 h, centrifuge, wash, dry, and calcine at 450°C for 2 h to obtain ZnO-deposited porous alumina nanospheres.
[0083] Comparative Example 4
[0084] Compared with Example 3, the difference is that steps S2 and S3 are not performed.
[0085] The details are as follows:
[0086] S1. Preparation of porous alumina nanospheres: 40 g aluminum sulfate and 80 g urea were added to 2 L water, 1.5 g hexadecyltrimethylammonium chloride was added, heated to 65°C, stirred for 40 min, the pH value of the solution was adjusted to 9.5, the stirring reaction was continued for 100 min, centrifuged, washed, dried, and calcined at 650°C for 1.5 h to obtain porous alumina nanospheres;
[0087] S2. Modification: 10 g of porous alumina nanospheres were added to 200 mL of ethanol, 4 g of a silane coupling agent was added, the mixture was heated to 45 ° C, stirred for 1.5 h, centrifuged, washed, and dried to obtain modified porous alumina nanospheres;
[0088] The silane coupling agent is a mixture of KH602 and KH792, with a mass ratio of 3:4;
[0089] S3. Hydrolysis: 10 g of modified porous alumina nanospheres were added to 100 mL of water and stirred for hydrolysis at 45 ° C for 8 h to obtain silica-coated modified porous alumina nanospheres;
[0090] S4. Graft modification of Teflon: 10 g of polytetrafluoroethylene powder was added to 200 mL of Augeo SL-191 solvent. Under irradiation conditions, the temperature was 125°C, the total irradiation dose was 13 kGy, 2.5 g of glycidyl methacrylate, 0.015 g of ammonium ferrous sulfate and 0.04 g of concentrated sulfuric acid were added, nitrogen was introduced, heated to 65°C, stirred for 4 h, and after the reaction was completed, extracted with acetone for 24 h and dried to obtain modified Teflon powder;
[0091] S5. Preparation of wear-resistant and rust-proof Teflon coating: 10 g of modified Teflon powder and 5 g of silica-coated modified porous alumina nanospheres were added to 75 g of Teflon primer, and the mixture was stirred for 11 h to obtain a wear-resistant and rust-proof Teflon coating.
[0092] Comparative Example 5
[0093] Compared with Example 3, the difference is that in step S7, the modified Teflon powder is replaced by an equal amount of polytetrafluoroethylene powder.
[0094] The details are as follows:
[0095] S1. Preparation of porous alumina nanospheres: 40 g aluminum sulfate and 80 g urea were added to 2 L water, 1.5 g hexadecyltrimethylammonium chloride was added, heated to 65°C, stirred for 40 min, the pH value of the solution was adjusted to 9.5, the stirring reaction was continued for 100 min, centrifuged, washed, dried, and calcined at 650°C for 1.5 h to obtain porous alumina nanospheres;
[0096] S2. Deposition of ZnO / Fe2O3: 10 g of porous alumina nanospheres were added to 200 mL of water, 2.5 g of zinc nitrate and 1.5 g of ferric nitrate were added, the mixture was stirred and mixed evenly, 5.5 g of citric acid was added, the mixture was heated to 90°C, stirred for 2 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to obtain ZnO / Fe2O3 deposited porous alumina nanospheres;
[0097] S3. Reduction: The ZnO / Fe2O3 deposited porous alumina nanospheres were heated to 1150°C and reduced with hydrogen for 3h to obtain Zn / Fe deposited porous alumina nanospheres;
[0098] S4. Modification: 10 g of Zn / Fe deposited porous alumina nanospheres were added to 200 mL of ethanol, 4 g of a silane coupling agent was added, the mixture was heated to 45 ° C, stirred for 1.5 h, centrifuged, washed, and dried to obtain modified Zn / Fe deposited porous alumina nanospheres;
[0099] The silane coupling agent is a mixture of KH602 and KH792, with a mass ratio of 3:4;
[0100] S5. Hydrolysis: 10 g of modified Zn / Fe deposited porous alumina nanospheres were added to 100 mL of water and stirred for hydrolysis at 45 ° C for 8 h to obtain silica-coated modified Zn / Fe deposited porous alumina nanospheres;
[0101] S6. Preparation of wear-resistant and rust-proof Teflon coating: 10 g of polytetrafluoroethylene powder and 5 g of silica-coated modified Zn / Fe deposited porous alumina nanospheres were added to 75 g of Teflon primer, and the mixture was stirred for 11 h to obtain a wear-resistant and rust-proof Teflon coating.
[0102] Test Example 1
[0103] The wear-resistant and rust-proof Teflon coatings prepared in Examples 1-5 and Comparative Examples 1-5 were sprayed onto the surface of stainless steel with a primer, with a thickness of about 20 μm. The wear resistance was tested on a reciprocating friction and wear tester using a GCr15 ball with a diameter of 4.5 mm as a counter-wear pair, with a load of 8.2 N and a test time of 15 min to test the wear rate. The scratch resistance was tested in accordance with the provisions of GB / T 92798-2008. The pencil hardness of the coating was determined in accordance with the provisions of GB / T 6739-2006. The adhesion of the paint film was tested in accordance with GB / T 9286-1998, and the test piece was divided into 5×5 small grids with a blade, and adhered with transparent tape. The tape was removed to observe the integrity of the paint film. The results are shown in Table 1.
[0104] Table 1
[0105] Group <![CDATA[Wear rate (×10 -4 mm 3 / N·m)]]> Hardness (H) Scratch resistance (kg) Adhesion (grade) Example 1 1.2 4 13 0 Example 2 1.0 4 13 0 Example 3 0.9 4 15 0 Example 4 3.5 3 11 1 Example 5 4.1 3 12 1 Comparative Example 1 12.1 2 9 2 Comparative Example 2 6.4 3 11 1 Comparative Example 3 6.9 3 11 1 Comparative Example 4 8.5 3 10 1 Comparative Example 5 59.8 1 6 3
[0106] It can be seen from the above table that the coatings prepared by the wear-resistant and rust-proof Teflon coatings prepared in Examples 1-3 of the present invention have good wear resistance and comprehensive performance.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a wear-resistant and rust-proof Teflon coating, characterized in that: The following steps are involved: S1. Preparation of porous alumina nanospheres: adding aluminum sulfate and urea to water, adding a porogen, heating and stirring the reaction, adjusting the pH value of the solution, continuing to stir the reaction, centrifuging, washing, drying, and calcining to obtain porous alumina nanospheres; the mass ratio of aluminum sulfate, urea, and porogen is 3-5:7-10:0.1-0.2; S2. ZnO / Fe2O3 deposition: adding porous alumina nanospheres to water, adding zinc salt and iron salt, stirring and mixing, adding citric acid, heating and stirring, centrifuging, washing, drying, and calcining to obtain ZnO / Fe2O3 deposited porous alumina nanospheres; the mass ratio of the porous alumina nanospheres, zinc salt, iron salt, and citric acid is 10:2-3:1-2:4-7; S3 reduction: The ZnO / Fe2O3 deposited porous alumina nanospheres were reduced by hydrogen to obtain Zn / Fe deposited porous alumina nanospheres; S4 modification: adding Zn / Fe deposited porous alumina nanospheres to ethanol, adding a silane coupling agent, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified Zn / Fe deposited porous alumina nanospheres; the mass ratio of the Zn / Fe deposited porous alumina nanospheres to the silane coupling agent is 10:3-5; S5. Hydrolysis: The modified Zn / Fe deposited porous alumina nanospheres were added to water and stirred for hydrolysis to obtain silica-coated modified Zn / Fe deposited porous alumina nanospheres; S6. Graft modification of Teflon: adding polytetrafluoroethylene powder to Augeo SL-191 solvent, adding glycidyl methacrylate, an inhibitor and a sensitizer under irradiation conditions, introducing an inert gas, heating and stirring the reaction, extracting with acetone after the reaction, and drying to obtain a modified Teflon powder; the mass ratio of the polytetrafluoroethylene powder, glycidyl methacrylate, inhibitor and sensitizer is 10:2-3:0.01-0.02:0.02-0.05; S7. Preparation of wear-resistant and rust-proof Teflon coating: adding modified Teflon powder and silica-coated modified Zn / Fe deposited porous alumina nanospheres to Teflon primer, stirring and reacting to obtain wear-resistant and rust-proof Teflon coating; the mass ratio of the modified Teflon powder, silica-coated modified Zn / Fe deposited porous alumina nanospheres and Teflon primer is 10:4-7:70-80.
2. The preparation method according to claim 1, characterized in that: In step S1, the porogen is selected from at least one of hexadecyltrimethylammonium chloride, hexadecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium bromide, the temperature of the heating and stirring reaction is 60-70°C, the time is 30-50min, the pH value of the solution is adjusted to 9-10, the time of continuing the stirring reaction is 90-120min, and the temperature of the calcination is 600-700°C, and the time is 1-2h.
3. The preparation method according to claim 1, characterized in that: The heating and stirring temperature in step S2 is 85-95° C., the heating and stirring time is 1-3 hours, the calcination temperature is 400-500° C., the calcination time is 1-3 hours, the zinc salt is zinc chloride or zinc nitrate, and the iron salt is at least one of ferric chloride, ferric nitrate, and ferric sulfate.
4. The preparation method according to claim 1, characterized in that: The temperature of hydrogen reduction in step S3 is 1100-1200° C. and the time is 2-4 hours.
5. The preparation method according to claim 1, characterized in that: The silane coupling agent in step S4 is at least one of KH550, KH602, and KH792.
6. The preparation method according to claim 5, characterized in that: The silane coupling agent is a mixture of KH602 and KH792 in a mass ratio of 2-4:3-5. The temperature of the heating and stirring reaction is 40-50° C. and the time is 1-2 hours.
7. The preparation method according to claim 1, characterized in that: The stirring hydrolysis in step S5 is carried out at a temperature of 40-50° C. and for a time of 7-10 h.
8. The preparation method according to claim 1, characterized in that: The temperature of the irradiation condition in step S6 is 100-150°C, the total irradiation dose is 12-15 kGy, the inhibitor is ammonium ferrous sulfate, the sensitizer is concentrated sulfuric acid, the temperature of the heating and stirring reaction is 60-70°C, and the time of the heating and stirring reaction is 3-5h.
9. The preparation method according to claim 1, characterized in that: The stirring reaction time in step S7 is 10-12 hours.
10. A wear-resistant and rust-proof Teflon coating, characterized in that: The wear-resistant and rust-proof Teflon coating is prepared by the preparation method of the wear-resistant and rust-proof Teflon coating according to any one of claims 1 to 9.
Citation Information
Patent Citations
Nano Fe or Fe2O3 composite powder coating Si3N4 granule and preparation thereof
CN101259532A
Preparation method of wear-resistant and anti-corrosion Teflon coating material, coatingmaterial and application method
CN113174169A
High-temperature-resistant cooker pigment and preparation method thereof
CN115584207A
Wear-resistant super-hydrophobic polycarbonate substrate and preparation method thereof
CN115895009A
Weather-resistant and corrosion-resistant metal fluorocarbon coating and preparation method thereof
CN115960496A
Cited By
Composite modified Teflon coating as well as preparation method and application thereof
CN120905967A